Literasi dan Edukasi Pembayaran Non Tunai Melalui Aplikasi QR Code Indonesian Standard (QRIS) Pada Kelompok Milenial - Eris Tri Kurniawti; Idah Zuhroh; Nazaruddin Malik (Studi Kasus Inovasi Ekonomi, 2021)
Digital financial transactions in Indonesia continue to show an increasing trend from year to year, with a sharp increase in the last 3 years.  Observing the acceleration of the implementastion of the development of non-cash transactions and to improve the payment system.  Bank Indonesia launced the Indonesia Standart Quick Response Code (QRIS) on 17 August 2019, which then  as of 1 Januari 2020 required all non-cash payments using QRIS.  QRIS is a QR Code standartd created by Bank Indonesia to facilitate digital payments throught server-based electronic money apllications, electronic wallets, and mobile banking.  The target of the QRIS application is for economic actors, especially those dominated by the millennial generation (students) who demand all aspects of their lives.  So that the literacy and education program for young people or millennials, especially students, regarding the QRIS payment system and also at several erchant in the academic community, the output that is to be achieved is the expansioan of the use of the QRIS application by merchants within the Faculty of Economics and Business.